Anatomic Connections of the Subgenual Cingulate Region. Issue 3 (20th June 2016) - Vergani, Francesco; Martino, Juan; Morris, Christopher; Attems, Johannes; Ashkan, Keyoumars; Dell'Acqua, Flavio
Abstract: BACKGROUND: The subgenual cingulate gyrus (SCG) has been proposed as a target for deep brain stimulation (DBS) in neuropsychiatric disorders, mainly major depression. Despite promising clinical results, the mechanism of action of DBS in this region is poorly understood. Knowledge of the connections of the SCG can elucidate the network involved by DBS in this area and can help refine the targeting for DBS electrode placement. OBJECTIVE: To investigate the anatomic connections of the SCG region. METHODS: An anatomic study of the connections of the SCG was performed on postmortem specimens and in vivo with MR diffusion imaging tractography. Postmortem dissections were performed according to the Klingler technique. Specimens were fixed in 10% formalin and frozen at −15°C for 2 weeks. After thawing, dissection was performed with blunt dissectors. Whole brain tractography was performed using spherical deconvolution tractography. RESULTS: Four main connections were found: (1) fibers of the cingulum, originating at the level of the SCG and terminating at the medial aspect of the temporal lobe (parahippocampal gyrus); (2) fibers running toward the base of the frontal lobe, connecting the SCG with frontopolar areas; (3) fibers running more laterally, converging onto the ventral striatum (nucleus accumbens); (4) fibers of the uncinate fasciculus, connecting the orbitofrontal with the anterior temporal region. CONCLUSION: The SCG shows a wide range of white matter connections with limbic, prefrontal, and mesiotemporal areas. These findings can help to explain the role of the SCG in DBS for psychiatric disorders.